The Development of Project-Based Teaching Modules on Movement Systems and Circulatory System Materials for Senior High School - Dian Pengestuti; Setiyo Prajoko; Ika Sukmawati (Universitas Tidar, 2023)
In the Merdeka Curriculum, planning for learning can be prepared optimally by making teaching modules. The purpose of this study was to determine the level of feasibility and teacher response to teaching modules for teachers on the material of the motion system and circulatory system based on projects based on the Merdeka Curriculum. This research is Research and development (R&D) with the ADDIE model, as for the stages carried out, namely: 1) Analyze (analysis), 2) Design (Planning), 3) Develop (Development), 4) Implement (Implementation), and 5) Evaluate (Evaluation). Data collection techniques using interviews and observations. The instruments used were interview sheets, teaching material expert validation, material expert validation, and teacher response questionnaires. The results of the feasibility of the products that have been developed in the form of teaching modules from the validation of teaching materials experts are 93.6% and the percentage of material experts is 97.5%. The results of the response test at the implementation stage carried out on a limited basis obtained results on the teaching module of 90.63%. Thus it can be concluded that the teaching module accompanied by the project-based student module that has been developed is feasible to be used by teachers to assist in the implementation of learning.